Understanding The Knowledge, Beliefs, And Practices of Samareños On Red Tide Phenomenon: Implicationsfor Sustainable Management (Journal of Namibian Studies : History Politics Culture, 2023)
The people of Samar are heavily dependent on coastal resources fortheir livelihoods. This dependence underscores the pivotal role that coastal ecosystemsplay in supporting the local community's well-being, especially as Samar bays areconsistently confronted with periodic occurrences of red tide. Given the paramountimportance of these resources to the people, understanding how they perceive andrespond to red tide becomes imperative. This study investigates the social dimensions ofred tide perception among Samareños to inform management strategies. A quantitativeapproach, employing a structured KBP scale was used to assess the level of knowledge,beliefs, and practices relative to red tide. The findings reveal a high level of scientificknowledge (mean: 4.36) among respondents, indicating their comprehensiveunderstanding of various aspects associated with the phenomenon. However,misconceptions persist regarding the effectiveness of cooking seashells to reduce red tidepotency. Participants also hold favorable beliefs (mean: 4.06), signifying positiveperceptions related to red tide. In terms of practices, respondents exhibit a high level ofvigilance with a mean rating of 4.21 during red tide events, refraining from consumingaffected seafood and implementing measures to prevent waste disposal into waterbodies, recognizing its association to its occurrences. While overall knowledge is high, thepresence of misconceptions highlights the need for targeted education andenvironmental campaigns to correct misconceptions. These efforts will further enhancethe community's understanding of the importance of sustainable practices and management, contributing to the long-term health of coastal ecosystems and the well- being of the local populace. In support of sustainable development, collaboration between local authorities and policymakers with the communities may be encouraged to seamlessly integrate these practices into local governance and disaster preparednessefforts, acknowledging the community's steadfast commitment to safety during red tide events.